2013
DOI: 10.1177/1357633x13487101
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Frequency of Patient Use of Internet-Based Telemedicine to Manage Cardiovascular Disease Risk

Abstract: We examined the frequency of use by patients of a web-based reporting system to monitor and control cardiovascular disease (CVD) risk factors. A total of 192 patients with intermediate or high CVD risk were categorized into four quartiles based on their frequency of use of the telemedicine reporting system over one year. The lowest frequency users (Quartile I) averaged 17 reporting days in one year and the highest frequency users (Quartile IV) averaged 211 reporting days in one year. Factors associated with mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…It can be an adaptable, accessible and attractive method for enabling patients to rapidly return to work. TCR improves attendance to CR, 9 decreases costs 10 and increases self-management skills, 11 leading to long-term benefits through continued exercise-based activity. 12 Three systematic reviews point out that TCR and hospital-based CR have similar benefits on cardiovascular risk factors and reduced morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…It can be an adaptable, accessible and attractive method for enabling patients to rapidly return to work. TCR improves attendance to CR, 9 decreases costs 10 and increases self-management skills, 11 leading to long-term benefits through continued exercise-based activity. 12 Three systematic reviews point out that TCR and hospital-based CR have similar benefits on cardiovascular risk factors and reduced morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Telemedicine is quick, convenient and user‐friendly (Szilagyi & Adams, ), and previous studies have shown that telemedicine could reduce cardiovascular risk in veterans (Melnyk et al., ) and promote tighter glycaemic control in patients with T2DM (Zhou et al., ). An Internet‐based telemedicine intervention for the management or patients with CVD resulted in decreases in the severity of systolic blood pressure and other CVD risk factors (Kothapalli, Bove, Santamore, Homko, & Kashem, ). We carried out a pilot study, prior to the study presented herein, using electronic messaging intervention and determined that medication adherence could be improved among outpatients with coronary artery disease (Fang & Li, ).…”
Section: Discussionmentioning
confidence: 99%
“…Educating patients on health problems motivates them to track their progress and engage more with their physicians, thereby improving their cardiovascular risk. 16 A systematic review conducted by Polisena et al showed that home telemonitoring can provide congestive heart failure (CHF) patients with improved clinical results compared to conventional treatment. Home telemonitoring was also found to decrease hospitalization rates, the number of emergency visits to the emergency room, reduce all-cause of CHFrelated events, and lower mortality rates.…”
Section: Patientsmentioning
confidence: 99%